2004
DOI: 10.1007/s10350-004-0683-z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Graciloplasty in Patients Born With an Anorectal Malformation

Abstract: Results of dynamic graciloplasty for fecal incontinence are reasonable for this specific group of patients with limited treatment options. Despite functional dynamic graciloplasty, the results are worse than those for the total group of patients with dynamic graciloplasty. Rectal sensitivity and type of malformation are prognostic factors for outcome and can be used to select patients for treatment with dynamic graciloplasty, thereby improving treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 33 publications
(41 reference statements)
0
14
1
2
Order By: Relevance
“…Fecal incontinence is far from being just a mechanical problem, as shown by the fact that only 7 of 10 patients with a technically functioning DGP ever experience satisfactory continence. 19,23 Dynamic graciloplasty is limited by the anatomical applicability of the gracilis muscle and the life of the pulse generator, whereas ABS causes ischemia of the bowel wall at operating pressures required to maintain continence, because of the circular design of its cuff. It is unlikely that control of liquid stool will be achieved using an artificial device without compromising blood supply, because the control of liquid stool requires a constant sphincter occlusion pressure equivalent to the intraluminal pressure of the bowel.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal incontinence is far from being just a mechanical problem, as shown by the fact that only 7 of 10 patients with a technically functioning DGP ever experience satisfactory continence. 19,23 Dynamic graciloplasty is limited by the anatomical applicability of the gracilis muscle and the life of the pulse generator, whereas ABS causes ischemia of the bowel wall at operating pressures required to maintain continence, because of the circular design of its cuff. It is unlikely that control of liquid stool will be achieved using an artificial device without compromising blood supply, because the control of liquid stool requires a constant sphincter occlusion pressure equivalent to the intraluminal pressure of the bowel.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of these strict inclusion criteria, most of the adult patients are not eligible for dynamic graciloplasty. 12 Therefore, the majority of patients have to cope with their fecal continence problems without the prospect of physical improvement.…”
mentioning
confidence: 99%
“…118 Dynamic graciloplasty is most appropriate for patients with extensive sphincter disruption precluding a surgical repair, severe neural damage, or congenital disorders, such as anal atresia. 119,120 The results of dynamic graciloplasty have been variable. Although moderately good results are reported from a small number of high-volume centers, multicenter trials that included less-experienced surgeons have shown a high morbidity and poorer functional outcome.…”
Section: Surgical Optionsmentioning
confidence: 98%